Relevance of Distributive Justice, Procedural Justice and Fairness in Workplace (International Journal of Food and Nutritional Sciences, 2022)
Employees are an important asset to any organization. Their dedication, hard work and commitment play a vital part in the success of an organization. If employees are expected to give their best at work and be efficient at the optimum level, then they need to be treated fairly, equally and with respect. The main objective of this research is to study and understand Distributive Justice, Procedural Justice and Fairness at workplace and to study its impact on the efficiency of the employees. Distributive and Procedural Justice have an impact in all kinds of institutions, such as hospitals, educational institutions, factories etc. This study aims to cover all these areas under a single term of “workplace” which applies to all kind of institutions, organizations, corporations, etc. Analytical Research Design has been employed to carry out research in the present study with the help of secondary data. To understand Distributive Justice thoroughly, the researcher has explained different approaches to distributive justice, such as John Rawl’s Theory, Utilitarianism, Egalitarianism and Libertarianism. The four important pillars on which Procedural Justice is based are discussed in this study. The thin line that distinguishes distributive justice from procedural justice has been included in this research. The present study explains the importance of Fair treatment in the workplace and the behavioral attitude of employees towards unfair treatment. The difference between equity and equality in a workplace has been explained in the present study. The implication of distributive justice, procedural justice and fair treatment of employees at workplace has also been discussed by the researcher.